Fiscal capacity and aid allocation: Domestic resource mobilization and foreign aid in developing countries - Aniket Bhushan; Yiagadeesen Samy (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper is part of a the UNRISD project on The Politics of Domestic Resource Mobilization. Its specific contribution is with regards to the interaction between fiscal performance and donor aid allocation in developing countries. While several studies have examined whether aid affects fiscal performance, there has been no systematic study of whether fiscal capacity and performance in developing countries has any impact on donor aid allocation decisions. This paper argues that the latter is an important issue, given that domestic resource mobilization (DRM) is being increasingly recognized as an important component of financing for development, and that some donors are beginning to pay more attention to taxation and fiscal capacity. After reviewing the fiscal performance and aid allocation literature, the paper discusses the results of a large N-analysis for the period 1992-2010 that augments a standard aid allocation model with fiscal variables. This preliminary analysis of overall bilateral and multilateral aid allocation leads to the conclusion that there is hardly any correlation between overall aid and fiscal performance and capacity. This analysis is complemented by discussing the recent fiscal performance data and donor involvement in taxation and public financial management (PFM) in four case study countries. These case studies allow an examination of donor-recipient relationships. Specifically, the authors calculate a tax effort index for recipient countries over the period 1990-2012 and examine trends in various fiscal performance metrics. The paper also highlights which donors are present in the case study countries, and what their perceptions of fiscal performance in these countries are. The analysis shows that there are important gaps in terms of donors delivering on their commitments to align with recipient country priorities and providing aid through country PFM systems.
Keywords: 330